Lack of pupils in German riding schools? A causal-analytical consideration of customer satisfaction in children and adolescents - Maike Kayser; Claudia Gille; Katrin Suttorp; Achim Spiller (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2012)
Not only the horse as a living creature, but also equestrian sport, has a positive influence on the general upbringing and development of young people. Although equestrian sport still exerts a strong fascination, it is becoming more difficult to inspire young people to take part in this time-consuming and costly sport. It is not only the equestrian sport which is affected by this - the majority of sport clubs offering different types of sport have registered diminishing member numbers. Especially those riding schools which consider themselves as being service providers in equestrian sport are confronted with the challenge of binding children and adolescents to their school for a longer term, thereby enabling the schools to manage themselves sustainably. The present study has, therefore, investigated the various factors which influence customer satisfaction in riding schools and their significance by using a structural equation model. A survey of 203 children and adolescents was undertaken in five different German riding schools. Customer satisfaction was particularly influenced by the design of the riding lessons and the school horses. The influence of the riding instructor however, was more indirect (acting over the direct impact on the design of the lessons and the school'horses) than direct. One most noticeable aspect of the results is the strong influence of customer satisfaction on recommendation behaviour.
Keywords: 330; customer satisfaction; customer loyalty; riding schools; Partial Least Squares (PLS); Pferdesport; Pferdesport; Jugendliche; Sportverband; Beziehungsmarketing; Kundenzufriedenheit; Virales Marketing; Partial-Least-Squares-Modell; Deutschland